From pandemics to portfolios: Long-term impacts of the 2009 H1N1 outbreak on household investment choices - Naijia Guo; Ka Yui Leung; Shumeng Zhang (Osaka University, Institute of Social and Economic Research (ISER), 2025)
This study examines how experiencing a pandemic affects household investment behaviors. By leveraging cross-state variations in the H1N1 mortality rate in 2009, our difference-in-differences analysis reveals interesting findings. Although the pandemic does not significantly affect stock market participation, it depresses the proportion of liquid assets invested in risky assets among households who participate in the stock market. This effect persists for up to eight years after the pandemic and is particularly pronounced among households characterized by higher risk aversion and greater income volatility. Analysis conducted using different datasets consistently suggests that the pandemic primarily influences portfolio choices through a shift in risk attitudes.
Keywords: D10; G11; I10; 330; Pandemic; Portfolio Choice; Rational Inattention; Risky Share; Risk Attitude